2011
DOI: 10.32508/stdj.v14i4.2003
|View full text |Cite
|
Sign up to set email alerts
|

An Approach of Ubiquitous Devices Using T-Engine in Vietnam

Abstract: The 21st century is the era of Ubiquitous Computing where computing devices are present everywhere in our lives. To satisfy the development of this tendency, many hardware platforms have been proposed for developing Ubiquitous devices. Among them, T-Engine, an open standardized development platform for embedded systems, is one of the most popular platforrms. It is nowadays compatible with embedded equipments for a wide range of fields. In Vietnam, T-Engine has just been introduced for 4 years. However, most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subsequently, the authors used a rosin-sizing agent and a water-borne rosin-copper compound to impregnate poplar wood. The results showed that the rosin could decrease the moisture absorption ability of wood and help improve the decay resistance of the wood (Li et al 2011;Nguyen and Li 2014). In particular, the rosin had a very high copper fixing efficiency in wood, and wood samples treated with the rosin-copper compound had a greater decay resistance, even after leaching (Nguyen et al 2012;Nguyen et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the authors used a rosin-sizing agent and a water-borne rosin-copper compound to impregnate poplar wood. The results showed that the rosin could decrease the moisture absorption ability of wood and help improve the decay resistance of the wood (Li et al 2011;Nguyen and Li 2014). In particular, the rosin had a very high copper fixing efficiency in wood, and wood samples treated with the rosin-copper compound had a greater decay resistance, even after leaching (Nguyen et al 2012;Nguyen et al 2013a).…”
Section: Introductionmentioning
confidence: 99%